Biology of Predatory Crickets (Metioche vittaticollis Stal.) (Orthoptera: Gryllidae) on the Brown Planthopper (Nilapavarta lugens Stal.) (Homoptera: Delphacidae) - Mochamad Fauzi; Sri Karindah; Suharsono (Contributions of Central Research Institute for Agriculture, 2022)
This research was studied biological aspects and survival rate of M. vittaticollis Stal. on brown planthopper. The experiment was conducted at the Laboratory of Entomology, Departement of Plant Pest and Disease, Agriculture Faculty, Brawijaya University in May to November 2005. The results showed that the percentage of the eggs M. vittaticollis that hatched was 70,5 %. Adult of M. vittaticollis color was dark brown to black. The forewings covers the abdomen. The long winged adults have hindwings almost twice as long as the abdomen. All legs were yellow to orange with tree segment of tarsus. The age of copulated adult was longer than the uncopulated adults. The age of female was longer than the male. The average of development period was 27,43 ± 3,32 days and the average of body length was 5,13 ± 0,34 mm. Adults female of M. vittaticollis consumed 7,89 ± 0,51 third instar nymphs of brown planthopper and the male consumed 6,02 ± 0,48 third instar nymphs of brown planthopper per day. The oviposition period was 17,1 ± 1,65 days and post oviposition period was iv 1,7 ± 0,66 days. The average fecundity was 42,72 ± 4,09 eggs. Female laid in average of 2,41 ± 05 eggs per day. The survival rate decreased during increasing the level of stage of M. vittaticollis. The survival rate of egg to the adult stage were 70,5 %, 55,5 %, 44 %, 35 % and 31,5 %. The survival rate of first nymph could not be attain 100 % due to the all egg did not hatch and continually decrease till fourth instar of nymph. The mortality of each instar of nymph usually occured during moulting or in few days after moulting.